Development of Tandem Ion Mobility Spectrometry with High-voltage Fragmentation Unit at Atmospheric Pressure for Explosives Detection - Kang-yi LIU; Tian-xin XIAN; Ling-feng LI; Yun-jing ZHANG; Xing-li HE; Peng LI (Zhipu Xuebao)
Trace explosive detection is an essential aspect for ensuring public safety. Ion mobility spectrometry (IMS) is an effective technique for detecting explosives and compounds related to explosives. IMS technique operating at atmospheric pressure has numerous advantages, including simple structure, clear spectra, high sensitivity, and fast analysis speed, making it widely applied in fields such as on-site detection of explosives. However, the limitations of traditional ion mobility spectra lie in their low resolution and lack of fine structural information, making it difficult to differentiate ions with similar mobility, which can easily lead to false positive results. To address this issue, referencing collision-induced dissociation (CID) in mass spectrometry, explosives can be similarly dissociated under atmospheric pressure through radio frequency strong electric fields. This process generates rich secondary fragment ions, conferring mobility spectra with structural information of the analyte. Through simulation studies of the electric field of the drift tube and optimization of several structural parameters of the fragmentation grid, a tandem ion mobility spectrometry with a dual ion gate structure was developed. By changing the switch status of the ion gate and fragmentation grid, this system is capable of selecting specific parent mobility ions for fragmentation under ambient pressure. Three representative substances, ammonium nitrate (AN), cyclotrimethylene trinitramine (RDX), and pentaerythritol tetranitrate (PETN), along with their dopants, were used to obtain primary mobility spectra of explosives under atmospheric pressure. Based on their mobility spectra, parent ions were separated and then subjected to strong electric field fragmentation to acquire secondary fragment ions. Under the conditions of 170 ℃ and atmospheric pressure, AN achieves a dissociation rate of 95% for the parent ion at a frequency of 2.6 MHz and a peak voltage of 900 V. The dissociation rates for the product ions [RDX+NO2]− of RDX and product ions [RDX+Cl]− of RDX doped with C2Cl6 are 93% and 15% at a frequency of 2.6 MHz and a peak voltage of 1 500 V, respectively. The dissociation rates for [PETN+NO3]− and [PETN+Cl]− are 54% and 48%, respectively. The degree of ion fragmentation is mainly influenced by the structural characteristics of the parent ions, while increasing the electric field and temperature further promote their fragmentation. Although introducing radio frequency electric fields may result in a certain degree of ion loss, the combination of secondary fragments and parent ion drift times provides additional chemical information for explosive detection, potentially reducing false positives in detection of explosive.